Potassium Salts of 2, 5‐Bis(trimethylsilyl)‐Germolide: Switching between Aromatic and Non‐Aromatic States. Issue 46 (11th July 2019) - Dong, Zhaowen; Schmidtmann, Marc; Müller, Thomas
Abstract: The reduction of a 1‐mesityl‐2, 5‐bis‐trimethylsilylchlorogermole8 with KC8 is reported. While the reaction with one equivalent of KC8 gave the dimer with a Ge−Ge bond10, excess of KC8 (four equivalents) resulted in the formation of the potassium salt of the germole dianion, 11 with reductive cleavage of the Ge−C bond. Careful reduction with two equivalents of KC8 in THF provided the potassium salt of the planar germolide5 . Its solid‐state structure revealed contact ion pairs with the potassium ion η 5 ‐coordinated to the germacyclopentadienide ring. The molecular structure of the anion indicates a high degree of cyclic electron delocalization, in agreement with results from DFT calculations. Separation of the ion pair by complexation of the potassium ions with 18‐crown‐6 triggers the isomerization to germolide6, which is characterized by a pyramidal coordination sphere of the germanium atom and a localized diene structure. The isomers5 and6 represent a rare example for a structurally manifested switch between a non‐aromatic and an aromatic state induced by an external stimulus, in this case the complexation of the counter cation. Abstract : Aromaticity becomes germane ; the germanium version of cyclopentadienide (Cp − ): The potassium salt of a planar aromatic germacyclopentadienide was synthesized. Complexation of the potassium cation with crown ether triggers the structural switch to the non‐planar isomer with a localized structure.